Relationship Violence During The Covid-19 Pandemic: A Systematic Literature Review - Obadyah, Ariel Barlian; Susilo, Daniel; Anugerah, Cendera Rizky; Karina, Vega; Kustiwa, Agus (Universitas Brawijaya, 2024)
This systematic literature review aims to analyze various studies on relationship violence during the COVID-19 pandemic. Data collection was conducted with sources from Crossref between 2020 and 2022. The keywords used were